2012
DOI: 10.1002/chem.201202358
|View full text |Cite
|
Sign up to set email alerts
|

Dendrimer Functionalization with a Membrane‐Interacting Domain of Herpes Simplex Virus Type 1: Towards Intracellular Delivery

Abstract: A poly(amide)-based dendrimer was synthesized and functionalized with the membrane-interacting peptide gH(625-644) (gH625) derived from the herpes simplex virus type 1 (HSV-1) envelope glycoprotein H, which has previously been shown to assist in delivering large cargoes across the cellular membrane. We demonstrate that the attachment of the gH625 peptide sequence to the termini of a dendrimer allows the conjugate to penetrate into the cellular matrix, whereas the unfunctionalized dendrimer is excluded from tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
70
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 60 publications
1
70
0
2
Order By: Relevance
“…7,8 The coupling of cell-penetrating peptides to MNPs provides a good strategy for a substantial improvement of cellular uptake, enabling them to deliver a large variety of cargo molecules for therapy and diagnosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 The coupling of cell-penetrating peptides to MNPs provides a good strategy for a substantial improvement of cellular uptake, enabling them to deliver a large variety of cargo molecules for therapy and diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 This peptide has proved to exhibit exceptional vector properties 9 and has been shown to be essentially internalized by a nonendocytic pathway avoiding endosomal entrapment. 7,[12][13][14][15][16][17] In recent studies, it was also shown to be able to cross the blood-brain barrier in vitro and in vivo. 18 gH625 is, therefore, a very good delivery vector 9 and its coupling to NPs may be exploited to change their internalization mechanism and in case of MNPs, to avoid or reduce their toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of advanced technologies for peptide identification and modification further supports the extensive application of peptides in the field of theranostics research. 31,32 We have previously demonstrated that gH625, a 19-residue peptide, is a membrane-perturbing domain 13 that interacts with model membranes, contributing to their merging 13 and is able to traverse the membrane bilayer and transport a cargo (quantum dots, liposomes, and dendrimers) 16,18,20 into the cytoplasm and across an in vitro model of the BBB. 19 Uptake studies suggested a nonactive translocation mechanism in crossing the lipid bilayer, which may vary depending on the cargo.…”
Section: Discussionmentioning
confidence: 99%
“…15 Further, gH625 has been used extensively for vector-mediated strategies that enable passage of a large variety of small molecules as well as proteins across cell membranes in vitro. [16][17][18][19][20] Conjugation of gH625 to the surface of nanoparticles also enhances their transport across the BBB, as previously demonstrated in an in vitro model of the BBB. 19 Whether or not multifunctional nanodevices, designed and tested in vitro, work properly in vivo in a mammalian host is still not fully understood.…”
mentioning
confidence: 99%
“…1,2,17,18 In particular, we recently reported the ability of gH625 peptide to transport quantum dots inside the cytoplasm in an efficient way and only partially involving endocytic pathways; 18 moreover, we reported its ability to enhance intracellular penetration of liposomes functionalized with the peptide on the external leaflet, 17 nanoparticles, 2 and dendrimers. 19 Compared with the TAT peptide, which mainly exploits the endocytic pathway, the viral membranotropic peptide gH625 crosses membrane bilayers mainly through a translocation mechanism.…”
Section: Introductionmentioning
confidence: 90%